2014
DOI: 10.4049/jimmunol.1302806
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Requirement for CD4+ T Cell Help for Adenovirus Vector–Elicited CD8+ T Cell Responses

Abstract: Despite the widespread use of replication-incompetent recombinant adenovirus (Ad) vectors as candidate vaccine platforms, the mechanism by which these vectors elicit CD8+ T cell responses remains poorly understood. Our data demonstrate that induction and maintenance of CD8+ T cell responses by Ad vector immunization is longitudinally dependent on CD4+ T cell help for a prolonged period of time. Depletion of CD4+ T cells in wild type mice within the first eight days following Ad immunization resulted in dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 75 publications
4
29
0
Order By: Relevance
“…This data would suggest that prior reports of reduced antigen clearance CD4 + T cell deficient animals might instead reflect insufficient expansion of an otherwise functional CD8 + T cell response (310). In this study, we demonstrate that CD4 + T cells are required at priming for optimal expansion of CD8 + T cell responses by Ad vector and poxvirus vector immunization, consistent with previous reports (13, 2022). Additionally, we identify a critical role for CD4 + T cells in driving acquisition of CD8 + T cell effector functions and preventing dysfunctional differentiation, in contrast to previous reports showing largely functional primary CD8 + T cell effector responses in the absence of CD4 + T cells (12, 1619).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This data would suggest that prior reports of reduced antigen clearance CD4 + T cell deficient animals might instead reflect insufficient expansion of an otherwise functional CD8 + T cell response (310). In this study, we demonstrate that CD4 + T cells are required at priming for optimal expansion of CD8 + T cell responses by Ad vector and poxvirus vector immunization, consistent with previous reports (13, 2022). Additionally, we identify a critical role for CD4 + T cells in driving acquisition of CD8 + T cell effector functions and preventing dysfunctional differentiation, in contrast to previous reports showing largely functional primary CD8 + T cell effector responses in the absence of CD4 + T cells (12, 1619).…”
Section: Discussionsupporting
confidence: 92%
“…This vaccination regimen generates small, but measurable, CD8 + T cell responses in the absence of CD4 + T cell help (13, 20, 21). Mice were depleted of CD4 + T cells by two sequential doses of the αCD4 antibody (clone GK1.5) beginning on the day prior to immunization and CD4 + T cell depletion was maintained by re-administration of the antibody every 21 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment of Ad5-induced T cell responses has been more focused on CD8 T cells, while relatively less is known about CD4 T cell responses elicited by Ad5 immunization. Previous studies have shown that CD4 T cells are critical for transgenespecific CD8 T cell and antibody responses elicited by Ad vector immunization (7)(8)(9). However, the phenotypic and functional properties of CD4 T cells induced by Ad vectors remain less well investigated.…”
mentioning
confidence: 99%